FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Pada Bursa Efek Indonesia Periode 2016 - 2018) - Titania Manik; Herry Laksito (Diponegoro Journal of Accounting, 2019)
The purpose of this study was to examine the relationship between auditor type, auditor cost, company size, company performance and gearing ratio as independent variables on audit quality. The audit quality is described using the actual audit hour ratio for audit hours determined and deemed adequate by the Ministry of Finance of the Republic of Indonesia. The control variable used in this study is the number of subsidiaries.The population in this study are all companies listed on the Indonesia Stock Exchange. The sample from this study is a manufacturing company listed on the Indonesia Stock Exchange in the period 2016 - 2018 which has been selected using a purposive sampling technique. The analytical method used in this study is multiple regression analysis.The result of this study indicate that the type of auditor has a negative effect on audit quality, audit fees has a possitive effect on audit quality, company size has a possitive effect on audit quality, company performance has no effect on audit quality, gearing ratio has a negative effect on audit quality.